First record of blister pearls in the oyster Hyotissa hyotis (Linné, 1758) from Pliocene deposits at Sidi Brahim, Lower Chelif Basin (north-west Algeria) - Khalili, Rachid; Vinn, Olev (Geologos, 2023)
Fossil pearls are rare but important palaeoecological indicators in proving the former presence of parasites. A single right valve of Hyotissa hyotis from the Pliocene of Sidi Brahim shows numerous blister pearls inside the adductor muscle imprint. At the same locality, numerous shells with smooth adductor scars and without any blisters, have been collected. The structures in the studied valve can be assigned to blister pearls with high confidence due to their similarity to other Cenozoic pearls from Austria. The blister pearls likely formed as a reaction to parasite infestation. It is possible that some parasites especially targeted areas associated with the adductor muscles in the oyster genus Hyotissa, because similar blister pearls have previously been described in a congeneric species, H. squarrosa, from the Miocene of Austria.